2005
DOI: 10.1097/01.ta.0000179956.55078.c0
|View full text |Cite
|
Sign up to set email alerts
|

The Literature Increasingly Supports Expectant (Conservative) Management of Renal Trauma — A Systematic Review

Abstract: Dozens of papers going back as far as 50 years seem to support the wider use of nonoperative therapy of renal injuries, although for unclear reasons, this approach is not yet universally accepted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 90 publications
1
117
0
7
Order By: Relevance
“…Santucci et al, in a systematic review of renal trauma, demonstrated a significant variation in complication rate between the series revised, ranging from 0 to 34%, with a mean of 10%. 9 It can be explained by the fact that the majority of the studies are retrospective and comprises a small number of patients. Another important bias is the lack of standardization in some definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Santucci et al, in a systematic review of renal trauma, demonstrated a significant variation in complication rate between the series revised, ranging from 0 to 34%, with a mean of 10%. 9 It can be explained by the fact that the majority of the studies are retrospective and comprises a small number of patients. Another important bias is the lack of standardization in some definitions.…”
Section: Discussionmentioning
confidence: 99%
“…The conservative management of blunt renal trauma was first proposed in the 1940s. [1] Since then the benefits of this approach have become increasingly apparent with reductions in nephrectomy rate, complications, and hospital stay all being reported. [1][2][3] There has been a paradigm shift towards conservative management for severe blunt trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since then the benefits of this approach have become increasingly apparent with reductions in nephrectomy rate, complications, and hospital stay all being reported. [1][2][3] There has been a paradigm shift towards conservative management for severe blunt trauma. [1,[4][5][6][7][8][9] Successful management of renal injury depends upon accurate assessment of their extent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations